2011
DOI: 10.2298/sarh1110619s
|View full text |Cite
|
Sign up to set email alerts
|

Histological types and age distribution of lung cancer operated patients over a 20-year period: A pathohistological based study

Abstract: SCC is the most frequent histological type of lung cancer found in all age groups and in both genders of surgically treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Results were consistent with the study conducted by Stojsic J et al, who found that the most patients operated for lung cancer were in the age group of 51-60 years. 11 In this study females were affected at younger age than males. The above findings were comparable with international studies.…”
Section: Discussionmentioning
confidence: 58%
“…Results were consistent with the study conducted by Stojsic J et al, who found that the most patients operated for lung cancer were in the age group of 51-60 years. 11 In this study females were affected at younger age than males. The above findings were comparable with international studies.…”
Section: Discussionmentioning
confidence: 58%
“…An active search is underway for the most efficient bronchoscopic imaging tool for the detection of cancer ( 13 , 14 ). Using bronchoscopic imaging to detect and investigate precancerous lesions in the bronchial mucosa may represent a turning point in the elucidation of neoplastic transformation ( 15 - 17 ). In the present study, there were no cases suspected of being MALT lymphoma prior to a bronchoscopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the incidence of lung cancer may also be attributed to the increased accuracy of pathological diagnosis, with the aid of immunohistochemical techniques. Many ADC cases that were previously difficult to identify can now be diagnosed, including poorly differentiated solid type ADC that were difficult to identify (23). Furthermore, ADC lesions are peripheral and are relatively simple to excise.…”
Section: Distribution Of the Pathological Types According To Sexmentioning
confidence: 99%